Mechanobiological Stimulations of Algal Cells for Energy Harvesting. Issue 6 (21st April 2021) - Song, Jihwan; Kim, Dongchoul; Lee, Luke P.
Abstract: Stimulation of microalgae enables high lipid productivity because the induced stress can lead to a change in the microalgal metabolism. However, existing systems based on the control of pH, temperature, or nitrogen that stimulate microalgae through a culture medium face difficulties in maintaining the stress or are accompanied by complicated procedures to exert this stress, which decreases the lipid productivity. Here, the mechanobiological stimulations of algal cells via effective collisions in a soft lattice and phototaxis system are presented for energy harvesting. An energy harvesting system with a soft lattice (i.e., a micropillar array) is designed, which radiates light through a waveguide. Numerical simulations show that the average number of collisions when the distance of the soft lattice is set to be 10 mm and the intensity of light is set to 30 W m −2 is increased by up to 300% than in conditions without light. However, more interestingly, this amplifying effect disappears when the distance of the soft lattice becomes significantly small (e.g., 0.1 mm) owing to the reduced gradient and excessively enhanced intensity of light by their superposition. This analysis provides important insights into the design of mechanobiological stimulation‐based energy harvesting systems of algal cells. Abstract : The mechanobiological stimulations of microalgae via effective collisions in a soft lattice and phototaxis system for energy harvesting are presented. The collisions in the soft lattice increase with the phototaxis. However, interestingly, this amplifying effect disappears unless the appropriate parameter of the soft lattice design is assured. It provides important insights into the design of mechanobiological stimulation‐based energy harvesting systems.